TANGGUNG JAWAB NOTARIS PEMEGANG PROTOKOL ATAS TIDAK DIBERIKANNYA SALINAN AKTA DAN MINUTA AKTA YANG TIDAK DITANDATANGANI SAKSI-SAKSI DAN NOTARIS SERTA DAMPAK HUKUMNYA TERHADAP PENGHADAP - Gunawan, Hendra; Iriantoro, Agung (Rechtsregel : Jurnal Ilmu Hukum, 2025)
This study examines the legal responsibility of notaries of protocol holders related to the absence of copies of deeds and minutes of formally defective deeds, with a case study of Decision Number 205/Pdt.G/2023/PN Amb. Notaries of protocol holders are responsible for the deeds they hold, even though their authority is limited and cannot correct invalid deeds. Deeds that witnesses and notaries do not sign have legal weaknesses, so they are only considered deeds underhand. In this case, the notary who holds the protocol can explain to the witness or suggest the creation of a new deed. The absence of a signature on the deed impacts the validity of the document and the legal interests of the plaintiff. In addition, the District Court's decision stating that the lawsuit is inadmissible (NO) shows that there is a formal defect in the lawsuit so that the defendant fails to obtain legal protection. This study emphasizes the importance of notary compliance with legal procedures in making and storing deeds to ensure legal certainty for related parties.